Evaluation of Availability and Use of Computer Systems and Accessories for Efficient Computer Instruction and Learning in Senior Secondary School - Gaga, Thomas; Onyemaechi, Madumere Smart (International Journal of Educational and Psychological Sciences, 2024)
This research is an evaluation of the availability and use of Computer Systems and Accessories for Efficient Computer Instruction and Learning in Senior Secondary school. The main objective of this research is to investigate on the availability of computer laboratories in the secondary school and the ways in which the students are carrying out practical’s with the computer system. Secondary and primary data were used in sourcing of data. Sample size was drawn from the total population. Tabulation and simple percentage was used in analyzing the data and chi-square statistical tool was adopted for its hypothesis. The findings indicated that the availability of computer system and accessories has significant impact on the efficient instruction and acquisition of computer skills in senior secondary school. It is recommended that senior secondary school equip their computer laboratories with the necessary computer accessories that will enhance effective learning and teaching of computer.